Identifying forms of social capital among onion farmers in Miagao, Iloilo a study on the Asosasyon sang mga manogsibuyas sa Miagao and its significance to agricultural development. - Santamaria, Toni Ann (2015.)
This study provides an overview of social capital which may exist in farmer organizations and its significance to agricultural development, particularly in production capacity. The research focuses on social capital in the context of Asosasyon sang mga Manogsibuyas sa Miagao (AMM), an association of onion farmers in the muncipality of Miagao, Iloilo. The association was initiated by the municipal government in 2011 to encourage collaboration among local farmers and national agricultural programs, and to keep up with the municipality's title as largest producer of bulb onion in Western Visayas since 2008; as attested by a study of Eastwest Seed Co., Miagao's onion seed supplier. Through the use of a simplified version of Woolcock and Nyhans-Jones' Mixed Methods, a combination of methods including key informant interviews, participatory techniques, and household surveys, the study was able to derive data that: (1) provided an in-depth description of the Asosyon sang mga Manogsibuyas sa Miagao (AMM); (2) identified the forms of social capital within the association; and (3) determined whether particular forms of social capital contributed to agricultural productivity of onion farmers. The study surveyed respondents and interviewed key informants from three barangays: Bagumbayan (barangay most closely associated with Eastwest Seed Co.), Durog (barangay with most population of onion farmers), and Tan-agan (barangay with least population of onion farmers). The findings revealed that: (a) majority of sampled onion farmers in Miagao are bound by kinship and family ties, and are therefore strong in cognitive social capital; (b) their organizational capacity is highly dependent on their partnership with the Department of Agriculture in the muncipal level and the Eastwest Co.' and is therfore reliant on their structural social capital; and (c) structural social capital positively affected production capacity since 2011 through the AMM, but the onion production decline in Miagao maybe largely attributed to reasons other than social capital - therefore signifying a weak, almost non-existent link between social capital and production capacity among onion farmers in Miagao, Iloilo.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Farmers, Onion -- Miagao, Iloilo